The Effect of Giving Cinnamon Decoated on Perineal Wound Pain in Post-Postpartum Women - Nasution, Pratiwi; Siregar, Afrahul Padilah; Zuiatna, Dian (Jurnal Keperawatan Priority, 2024)
Every mother who has undergone the birth process with a perineal wound will feel pain, the pain felt causes unpleasant impacts such as pain and fear. Cases of this infection (25 - 55%) are caused by infection of the birth canal due to episiotomy or spontaneous tearing, mostly with complaints of pain in the area or for fear of the stitches falling out. To reduce perineal pain, one of them is consuming Cinnamon decoction. To see whether there is an effect of giving Cinnamon decoction on perineal wound pain in postpartum women at the Deby Cyntia Medan practice in 2023. Method research design using pre-experiment, with a One Group Pretest Posttest design. The research population was 10 postpartum mothers who experienced a second degree tear in the birth canal who experienced pain. The sampling technique for this research used purposive sampling of 10 people, data analysis used univariate and bivariate analysis using the Willcoxon test. The results is value is (p = 0.004 < 0.050), so it can be concluded that there is an effect of giving Cinnamon decoction on perineal wound pain in postpartum women at the practice. There is an effect of giving Cinnamon decoction on perineal wound pain in postpartum women at the Medan Deby Chyntia Midwife Practice in 2023. It is recommended for research sites, especially health workers, to encourage postpartum mothers to consume Cinnamon decoction as an alternative for non-pharmacological treatment of perineal wounds.